Mesenchymal Stem Cells Manage Endogenous Tissue Regeneration - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2016)
BACKGROUND: Current findings set a new understanding that every adult tissue has its own intrinsic progenitor or stem cell, give a potency for their innate turnover dynamics. This broke the old assumption that adult tissues cannot regenerate themselves. Localized tissue regeneration was regulatory oversight by a separate class of local cells originating as perivascular cells, suggested a profound influence on using specific cells for cell therapies as a health care delivery tool set.CONTENT: The mesenchymal stem cell (MSC) could be mobilized from the marrow or other depots or can be culture-expanded MSCs which are delivered to the damage site either by direct or systemic injection. MSCs act paracrine and autocrine by inducing a variety of cytokines and growth factors which suppress local immune system, inhibit fibrosis (scar formation) and apoptosis, enhanceangiogenesis, and stimulate mitosis and differentiation of tissue, intrinsic reparative or stem cells. These referred a trophic effects, different from the direct differentiation of MSCs into repair tissue. Thus, MSC suggested as a multidrug delivery vehicles in response of injury. In this regard, the trophic effects of MSCs may have profound clinical use.SUMMARY: Managing the body’s natural repair and regeneration capacities is the new frontier for modern medicine and the basis for the science of cell therapies. Study of MSCs become one avenue that being pursued to explore the endogenous tissue regeneration management, so that people have a great expectation to solve many severe diseases.KEYWORDS: mesenchymal stromal/stem cell, paracrine or autocrine activities, trophic mediator, inflammation, wound healing